EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) PADA DINASS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASSET DAERAH KOTA KOTAMOBAGU - Komaling, Veybie; Walandow, Stanley Kho (Universitas Sam Ratulangi, 2015)
Computer Applications SIMDA program is an application program that is intended to assist local governments in the area of financial management. As for the above purpose of the research is to evaluate the application of SIMDA at the Department of Revenue, Finance and Asset Management Regional Kotamobagu. Research methods using qualitative data, that is data obtained from the object of research in the form of sentences or descriptions, sketches and drawings and quantitative data, ie data obtained from the object of research in the form of numbers or numbers that have been processed further. From this study, the researchers concluded that SIMDA Application Evaluation in the Department of Revenue, Finance and Asset Management Regional Kotamobagu not fully in accordance with the Legislation in force, because the procedure is not in accordance with the cash outlay Minister Regulation No. 13 Year 2006 on Guidelines for Financial Management area.